Enhancing the role and visibility of forests and the forest sector in Uganda’s sustainable development - Uganda Wildlife Society (Uganda Wildlife Society, 2011)
Forests according to FAO global forest resources assessment 2010, is defined as land spanning more than 0.5 hectares with trees higher than 5 meters, a canopy cover of more than 10% or trees able to reach these thresholds in situ. Forests among others perform the critical functions of sustaining production in agro ecosystems, energy sources, different land uses and environment quality, including climate. Seventeen percent of Uganda’s total land area is forests. Over 60% of Uganda’s forests are in land privately owned by individuals or institutions, and the remaining constitute central forest reserves (506 in total) managed by the National Forest authority and district forest reserves under the jurisdiction of local governments.